2017
DOI: 10.1177/1471301217735180
|View full text |Cite
|
Sign up to set email alerts
|

Electronic memory aids for people with dementia experiencing prospective memory loss: A review of empirical studies

Abstract: This paper details a review of the literature on the use of electronic aids for prospective memory for people with dementia. Key findings of the review are that: electronic memory aids show potential for supporting people's prospective memory but the devices and software applications need further development in order to function reliably; sample sizes of studies are often very small, limiting the generalisability of their findings; few studies of devices are conducted in users' home environments; and most of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 53 publications
1
23
0
Order By: Relevance
“…From an empirical perspective, a number of studies investigated the role of assistive technology in fostering memory and other abilities in PwD (137), with recent work also summarizing results in relation to electronic devices (138). Findings have indicated that improvements can be seen in various abilities, even in cases of severe dementia [e.g., (139)], but it has been suggested that the focus of the studies needs to be expanded.…”
Section: Extended Selfmentioning
confidence: 99%
See 1 more Smart Citation
“…From an empirical perspective, a number of studies investigated the role of assistive technology in fostering memory and other abilities in PwD (137), with recent work also summarizing results in relation to electronic devices (138). Findings have indicated that improvements can be seen in various abilities, even in cases of severe dementia [e.g., (139)], but it has been suggested that the focus of the studies needs to be expanded.…”
Section: Extended Selfmentioning
confidence: 99%
“…Findings have indicated that improvements can be seen in various abilities, even in cases of severe dementia [e.g., (139)], but it has been suggested that the focus of the studies needs to be expanded. Specifically, most devices are used to improve ability to undertake tasks, with less attention paid to quality of life, behavioral issues, social connectedness, and recreational activities (138,139). It has been argued that assistive technologies should be used in PwD to foster social engagement and decision making, which have an important impact on personhood in dementia (140).…”
Section: Extended Selfmentioning
confidence: 99%
“…Examining the works reported in Sections 1 and 2, for applications of sound as memory stimulus, it was observed that only a few works exist. In Table 1, the previous works are reported (as referenced in [35]). The number of participating persons was small, and in the cases that more than three people participated in the evaluation, training was required; thus, a larger sample size was necessary.…”
Section: Set Of Testsmentioning
confidence: 99%
“…Recent reviews and position papers, addressing AT for people with dementia from a broad perspective, generally come to concurrent conclusions regarding a range of topics to be addressed in order to make advances in research and bring to market evidence-based solutions that are usable and effective in everyday lives of people with dementia (Bächle et al, 2018;Holthe et al, 2018;Ienca et al, 2017;Kenigsberg et al, 2017;King and Dwan, 2017;Meiland et al, 2017;Robillard et al, 2018). Among the most recurrent is the recommendation to involve people with dementia in the design and testing of AT, to make sure that their needs, preferences, and capacities are met and also to pursue this end user perspective when developing applicable and effective methods for dissemination and adoption of AT.…”
Section: Introductionmentioning
confidence: 99%